Evasive Neutral 2‐Aza‐Cope Rearrangements. Kinetic and Computational Studies with Cyclic Nitrones1. Issue 25 (22nd July 2013) - Delso, Ignacio; Melicchio, Alessandro; Isasi, Arantzazu; Tejero, Tomás; Merino, Pedro
Abstract: A full experimental study of the activation energy required for the hitherto unknown neutral 2‐aza‐Cope rearrangement is presented. A kinetic study of the process showed activation energies in the range of 22.91–24.06 kcal/mol, in agreement with a process operating at moderate temperature (70 °C). Calculations at B3LYP/6‐311+G(d, p) and M06‐2X/6‐311+G(d, p) levels of theory considering solvent (dimethyl sulfoxide (DMSO) and toluene) effects (PCM model) predict reaction energy barriers that are in agreement with the values obtained from 1 H NMR‐based kinetic experiments. Results obtained by using enantiomerically pure substrates demonstrate that the rearrangement takes place with complete transfer of chirality, in contrast to previously described cationic processes. The effects of solvent and acid catalysis, which converts the process into the more common cationic rearrangement, have also been studied. DFT calculations also predict correctly the acceleration of the process under acid catalysis, estimating energy barriers in the range of 16.80–18.57 kcal/mol. Abstract : The hitherto unknown neutral 2‐aza‐Cope rearrangement of nitrones takes place under thermal conditions with complete transfer of chirality. The process can be catalyzed by acid through a classical cationic 2‐aza‐Cope rearrangement. Kinetic 1 H NMR experiments and DFT theoretical studies have been used to estimate the activation parameters and determine the energy of activation of the process.